Реформування сучасної міжнародної валютної системи в правовому контексті : проблеми та перспективи. - Якубовська, Н.О.; Якубовская, Н.О.; Jakubovskaja, N (My University, 2012)
The paper studies the possibilities for the reforming of international mon- etary system in following scenarios: by saving the system, based on U.S. dol- lars; by the creation of multicurrency system; by the establishment of supra- national currency. It analyzes the international monetary system current legal framework suitability to realize the proposed reforms. The suggestions for changes and amendments to the existing legal framework of international monetary system are made.
Якубовська Н.О. Реформування сучасної міжнародної валютної системи в правовому контексті : проблеми та перспективи. / Н.О. Якубовська //Актуальні проблеми політики : зб. наук. пр. / гол. ред. С. В. Ківалов ; відп. за вип. Л. І. Кормич. – Одеса : Національний університет "Одеська юридична академія" : Південноукраїнський центр гендерних проблем, 2012. – Вип. 44. – C. 191 - 200.
Keywords: Реформування сучасної міжнародної валютної системи; Мужнародна валютна система; Правові основи функціонування міжнародної валютної системи; Правовые основы функционирования международной валютной системы; Международная валютная система; Реформирование современой международной валютной системы; The reform of the modern international monetary system; International monetary system; Legal basis for the functioning of the international monetary system